En conversation avec la mort. Tommy J. Curry et les discours philosophiques de la masculinité noire - Norman Ajari (Itinéraires)
In the current philosophy of race and critical theory of racism, it is not self-evident to consider black men as producers of discourse and theory. It is as if we have unlearned to see them and their social position has been rendered uninhabitable for thought. This article questions this situation by drawing on the ideas of contemporary African-American philosopher Tommy J. Curry. Although black men are among the poorest, least socially mobile, and most massively discriminated against and incarcerated demographic groups in the United States of America, black masculinity is a priori disqualified as a locus of enunciation, because current gender studies and feminist theory assume that they enjoy some social privilege because of their gender. A kind of double bind runs through black and intersectional feminist thinking on the issue: on the one hand, it claims to refuse to universalise the categories of masculine and feminine, but on the other hand it always interprets black positions through an analogy with the positions of white women and men. The aim is to show how Curry's original argument and the field of study she initiated, Black male studies, allow us to think about the irreducible specificity of the place of enunciation of black men, beyond their assignation to what Fanon called the zone of non-being.